Pengembangan LKS dalam Pembelajaran Matematika untuk Peserta Didik Tunagrahita - Yunita Utami; Maya Nurfitriyanti (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The purpose of this study is to develop teaching materials mathematics in the form of Student Worksheet (LKS) for learners tunagrahita. To develop the instructional media the Instructional Development Model was developed which consisted of several steps: at the beginning of the study identifying instructional needs, both doing instructional analysis, identifying the three behaviors and the initial characteristics of the learner, the four writing the specific instructional objectives, the fifth composing the results assessment tool, the sixth formulate instructional strategies, seventh develop instructional materials, evaluate and revise eighth. Based on the analysis and discussion, the development of LKS is suitable for supporting the learning of mathematics of the students of tunagrahita. It is based on the test results of Language experts, development experts, material experts and psychologists. In experimental language test results, the teaching material is declared good because the explanatory text in the teaching materials is easy to understand. In the test results 2 development experts stated good teaching materials with a percentage of 83.3% and 73.3% respectively. In the test results 2 material experts declared good teaching materials with a percentage of 85% and 81.7% respectively. While the test of psychology experts both stated good teaching materials with 80% percentage.